The colors of biomass burning aerosols in the atmosphere - Liu, Chao (Sci Rep, 2016)
Biomass burning aerosols mainly consist of black carbon (BC) and organic aerosols (OAs), and some of OAs are brown carbon (BrC). This study simulates the colors of BrC, BC and their mixture with scattering OAs in the ambient atmosphere by using a combination of light scattering simulations, a two-stream radiative transfer model and a RGB (Red, Green, Blue) color model. We find that both BCs and tar balls (a class of BrC) appear brownish at small particle sizes and blackish at large sizes. This is because the aerosol absorption Ångström exponent (AAE) largely controls the color and larger particles give smaller AAE values. At realistic size distributions, BCs look more blackish than tar balls, but still exhibit some brown color. However, when the absorptance of aerosol layer at green wavelength becomes larger than approximately 0.8, all biomass burning aerosols look blackish. The colors for mixture of purely scattering and absorptive carbonaceous aerosol layers in the atmosphere are also investigated. We suggest that the brownishness of biomass burning aerosols indicates the amount of BC/BrC as well as the ratio of BC to BrC.